Effect of Occupational and Psychological Factors in Back Pain Nurses in AMOL City - Seyyed Hamid Sharif Nia; Ali Akbar Hagh-Doust; Fatemeh Haji-Hosseini; Hamid Hojjati; Mitra Javan-Amoli (University of Social Welfare and Rehabilitation Sciences, 2012)
Objective: The aim of this investigation is recognizing the job and psychic factors of the job with Amol nurses backache. Materials & Methods: This study was conducted on 400 nurses in some public hospitals in Amol. Colleting the information was done through the modified Nordic questionnaire and the given analysis was through the descriptive statistics, chi-square, independent t-test and Logistic regression. Results: 324 of the nurses (81%) had backache at least once during the previous year. Their average age was 32.39±6.2 years and their average height was 166.7±8.7cm and their average weight was 67.7±9.8. Female gender (OR=3.03), regular exercise (OR=0.4), increased height per centimeter (OR=1.06) and increased weight per kg (OR=1.04) communication means do with back pain showed. Bending for lifting objects from the floor for 5% risk of back pain increases and the work related psychosocial factors were observed for each one degree increase in the intensity of dissatisfaction with colleagues back pain risk is increased 70% and between job stress factors, for every one degree increase in the range (always, most often, sometimes, never) in a hurry to work 40% less likely to back pain. Conclusion: The findings of this study confirm nurses lumbar injuries are at risk. Also be significant for some individual factors, physical and psychological complexity suggests occupational back pain back pain are factors that can modify their costs into the system and reduce the individual.